A narrative review of anxiety regulation in PhD students based on Green model - Ma, Yue; Yu, Ahui; Ma, Haiqi; Zhao, Yang; Liu, Xiaojun; Zhai, Huimin; Gao, Yulin (Frontiers in Psychology, 2024)
To gain a better understanding of the factors that contribute to anxiety among PhD students and the reasons for poor regulation in the current situation, this paper analyses the existing literature on anxiety among PhD students using Green's model. It also compares and evaluates various methods of regulating anxiety. The literature review to extract information on the causes and levels of anxiety, methods and outcomes of anxiety intervention and regulation, and to make comparisons. The study reveals that the phenomenon of PhD students' anxiety has intensified globally in recent years, especially after the end of the epidemic. PhD students experience anxiety due to research pressure, economic pressure, future development, and interpersonal pressure. The main influencing factors are currently the relationship with the supervisor, development prospects, social support, and peer comparison. Among the stress relief methods, the regulation of self-relaxation was found to have better effects on mild anxiety, such as positive thinking, meditation, yoga and physical exercise can be helpful for emotion release then help focus on problem solved. Whereas severe anxiety may require institutional and pharmacological support, also including using psychological therapy such as behavioral cognitive therapy and systematic desensitization methods. For university, competence to provide course-assisted guidance, such as writing groups, peer support, and time management, is also important. Academic communities should pay attention to the guidance on academic fairness. However, PhD students are often unaware of the resources available to them for coping with stress and may not take the initiative to seek psychological counseling or institutional assistance. Therefore, PhD students should receive support from various sources, be guided to express their thoughts, and receive additional education and academic assistance to manage stress. This will enhance their confidence and aid in improving their scientific research.